Impact of a large load of aerobic character with the use of movement on roller skis on the functional state of the body of racing skier 15–16 years - Таран, Лариса (Slobozhanskyi Herald of Science and Sport, 2017)
Larysa Taran Purpose: determine the nature of the course and the timing of recovery as a result of the impact of a large load of aerobic orientation with the use of movement on the roller skis on the functional state of the organism of young racing skier aged 15–16. Material & Methods: in the studies took part the young racing skier of 15–16 years (I, II sports category) of the age group "younger boys". Before the beginning of the training sessions, the subjects registered a set of indicators that allowed assessing the functional state of the organism (cardiovascular, respiratory and neuromuscular systems). Repeatedly recorded the studied indicators for the same complex after the end of training sessions after 1 hour, as well as after 24, 48 and 72 hours. Results: the young racing skier based on the results of the conducted studies analyzed the dynamics of indicators of the functional state of the organism. The timing of restoration of the cardiovascular, respiratory and neuromuscular systems has been established, which must be taken into account when planning the training process in microcycles. Conclusion: as a result of studies on the effect of heavy loads using the movement on skiing rollers, a decrease in the functional parameters of the cardiovascular, respiratory, neuromuscular systems of the body was established. The recovery period as a whole lasted for 72 hours. At the same time, it was revealed that the anaerobic metabolic capacity was restored after 48 hours.